Pendampingan Olimpiade IPA Berbasis Strategi Pemecahan Masalah Pada Siswa SMP Muhammadiyah At-Tanwir Metro - ALFARISI, MUHAMAD ALFARISI; Rosa Prasasti, Adya (Jurnal Pengabdian Masyarakat Sains Indonesia (Indonesian Journal Of Science Community Services), 2024)
Muhammadiyah At-Tanwir Metro Middle School is a private school that is currently developing in Metro City. There is a need to increase student achievement in academic matters, especially science olympiads, Muhammadiyah At-Tanwir Metro Middle School has implemented olympiad guidance specifically for students who are talented in the field of science. Students' achievements in their respective science olympiads are very minimal, this is the focus point in the assistance we provide. The aim of accompanying the Olympics at Muhammadiyah At-Tanwir Metro Middle School is to maximize the students' training process. This Olympic guidance is a manifestation of the school's collaboration with the service team. The school considers that there is a need for development of the dedication for olympiad guidance that has been implemented, namely in aspects of science problem solving strategies that teachers and students themselves need to know. This problem solving strategy is important to support students in participating in the Science Olympiad. The expected output from this service activity is an Olympic material module based on the Polya strategy as well as notes on the results of developing Science Olympiad Material for Muhamamdiyah Middle School At-Tanwir Metro.